Improving the functional capabilities of schoolchildren aged 7–11 with respiratory diseases - Sablin, A.B.; Aleskerov, R.R.; Ulyanova, E.A.; Latak, A.I. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to improve the functional abilities of primary school children with respiratory diseases through physical exercise. Methods and structure of the study. The pedagogical experiment was conducted from 13 January to 16 April 2025 in a specialised therapeutic physical education hall. Children from the experimental group visited the Moscow Kinesitherapy Centre three times a week and performed special sets of physical exercises for the respiratory system for 60 minutes. The overall endurance of the schoolchildren was determined by a 6-minute run test, the Stange and Genchi tests were used to measure the body's oxygen saturation, and spirometry was used to measure vital lung capacity. Results and conclusions. To evaluate the effectiveness of the experimental technique with schoolchildren aged 7-11, functional tests and test tasks were used, which were conducted before and after the experiment (assessment of overall endurance, oxygen saturation and vital capacity of the lungs). Before the start of the study, the groups were homogeneous, and the indicators did not have statistically significant differences (p>0.05). As a result of the study, the indicators in the control group became higher, but not significantly (p>0.05), while in the experimental group, the indicators in the 6-minute run test improved by 11.4%, in the breath-holding test, the indicators became higher by 13.8% and 16.8%, respectively, and in spirometry, the data increased by 19.2% (p<0.05).